2006
DOI: 10.1093/ps/85.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Natuphos and Phyzyme as Phytase Sources for Commercial Layers Fed Corn-Soy Diet

Abstract: The objective of this experiment was to compare the effects of 2 sources of phytase on performance of commercial Leghorns fed corn-soy diets. Seven diets were fed to Hy-line W-36 hens (n = 840; 8 replicates of 15 hens per treatment) from 21 to 33 wk of age. The treatments consisted of a control diet containing 0.38% nonphytate P (NPP) and a 2 x 3 factorial arrangement of 2 dietary NPP concentrations (0.11 and 0.26%) with 2 phytase sources [Natuphos (BASF, Mt. Olive, NJ) and Phyzyme (Danisco Animal Nutrition, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 14 publications
7
23
0
8
Order By: Relevance
“…The results of production and egg mass in relation to the level of available phosphorus were improved with the addition of phytase at 600 FTU, which agrees with the results already reported by Wu et al (2006) when they found an increase in production and egg mass of hens fed deficient-in-P diets (0.11% available P) supplemented with 300 UF/kg, reaching values similar to those birds fed control diet (0.38% available P).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The results of production and egg mass in relation to the level of available phosphorus were improved with the addition of phytase at 600 FTU, which agrees with the results already reported by Wu et al (2006) when they found an increase in production and egg mass of hens fed deficient-in-P diets (0.11% available P) supplemented with 300 UF/kg, reaching values similar to those birds fed control diet (0.38% available P).…”
Section: Resultssupporting
confidence: 91%
“…In contrast, Wu et al (2006) comments on his findings that the reduction of available phosphorus in the diet caused a reduction in feed intake, but when phytase was added to the experimental diets, consumption was improved, although it had been placed below the control diet.…”
Section: Resultsmentioning
confidence: 99%
“…Keshavarz (2003), no entanto, observaram que houve redução no consumo de ração quando as aves receberam dieta com baixos teores de fósforo disponível (0,2 e 0,1%) e que o consumo foi restabelecido com a suplementação de fitase na ração (150 ou 300 UF). Similarmente, Wu et al (2006) observaram que a redução do fósforo disponível da dieta (de 0,38% para 0,26 e 0,11%) provocou redução no consumo de ração, mas que, quando a fitase foi adicionada às rações, o consumo melhorou, embora ainda tenha ficado abaixo dos valores obtidos com a dieta controle.…”
Section: Consumo De Ração (G) Produção De Ovos (%)unclassified
“…Entretanto, a suplementação das dietas com fósforo inorgânico, além do alto custo, pode ocasionar problemas ambientais (Wu et al, 2006). Em áreas com alta densidade de criação de aves comerciais, o fósforo presente nas excretas apresenta elevado potencial de poluição (Smith et al, 2001) e pode prejudicar a qualidade do solo e da água.…”
Section: Introductionunclassified
See 1 more Smart Citation